THE INTERCONNECTION OF "MARKER" OF DISEASE AND ANTROPOFIZIOMETRICHESKIH INDICATORS OF YOUTHS OF MILITARY AGE IN ECOLOGICAL ZONES OF THE REPUBLIC OF DAGESTAN - O. M. Tumalaeva; M. G. Magomedov (Юг России: экология, развитие)
By results of analyses of interdependency anthropolo-physiometric indices and priority –“marking” for military age youth pathology conditions are given the estimation of deviation morphofunctional development and indices of sick rate in youth on high altitude zones of Daghestan Republic in dynamics for 10 years.